Toxoplasma gondii infection-induced host cellular DNA damage is strain-dependent and leads to the activation of the ATM-dependent homologous recombination pathway - Rojas-Barón, Lisbeth; Hermosilla, Carlos; Taubert, Anja; Velásquez, Zahady D. (Frontiers in Cellular and Infection Microbiology, 2024)
Toxoplasma gondii is a globally occurring apicomplexan parasite that infects humans and animals. Globally, different typical and atypical haplotypes of T. gondii induce varying pathologies in hosts. As an obligate intracellular protozoon, T. gondii was shown to interfere with host cell cycle progression, leading to mitotic spindle alteration, chromosome segregation errors and cytokinesis failure which all may reflect chromosomal instability. Referring to straindependent virulence, we here studied the potential of different T. gondii strains (RH, Me49 and NED) to drive DNA damage in primary endothelial host cells. Utilizing microscopic analyses, comet assays and γ-H2AX quantification, we demonstrated a strain-dependent induction of host cell binucleation, DNA damage and DNA double strand breaks, respectively, in T. gondiiinfected cells with the RH strain driving the most prominent effects. Interestingly, only the NED strain significantly triggered micronuclei formation in T. gondii-infected cells. Focusing on the RH strain, we furthermore demonstrated that T. gondii-infected primary host cells showed a DNA damage response by activating the ATM-dependent homologous recombination (HR) pathway. In contrast, key molecules of the nonhomologous DNA end joining (NHEJ) pathway were either not affected or downregulated in RH-infected host cells suggesting that this pathway is not activated by infection. In conclusion, current finding suggests that T. gondii infection affects the host cell genome integrity in a strain-dependent manner by causing DNA damage and chromosomal instability.